The day of battle : the war in Sicily and Italy, 1943-1944 - Atkinson, Rick. (New York : Henry Holt, 2007)
The second volume in a trilogy chronicling the liberation of Europe during World War II focuses on the Allied campaigns in Sicily and Italy, detailing the bloody battles at Salerno, Anzio, and Monte Cassino, as well as the June 1944 liberation of Rome.
1: Across the Middle Sea -- The burning shore -- An island redoubt -- 2: Salerno -- Corpse of the siren -- Winter -- 3: A river and a rock -- Perdition -- The murder space -- 4: Four horsemen -- A kettle of grief -- The great prize.
Map on lining papers.
Keywords: World War, 1939-1945 -- Campaigns -- Italy; Tweede Wereldoorlog; Bevrijding (Tweede Wereldoorlog); Weltkrieg (1939-1945); Italy -- History, Military -- 1914-1945.; Italien; Sizilien